A systematic process for using federal aid to support bridge preventive maintenance - Adams, Teresa M.; Pincheira, Jose A.; Kang, Myungook (Midwest Regional University Transportation Center, 2008)
Preventive maintenance (PM) is recognized as a cost?effective way to preserve the investment in and service life of highway bridges. State agencies, including Wisconsin, are performing bridge PM projects. SAFETEA-LU 23 U.S.C. 144(d) made States eligible to use Federal Highway Bridge Program (HBP) funds to support bridge preventive maintenance provided they demonstrate a systematic process for the PM program. Each State is to work with their Federal Highway Administration (FHWA) Division Office to document and approve the systematic process. Some State?s applications are successful and others are not. This report discusses concepts and essential characteristics of a systematic process for bridge PM with examples. The information presented herein was prepared based upon conversations with the FHWA Offices of Asset Management and Bridge Technology and by review of documents describing the successfully approved bridge PM programs of eight State transportation agencies. To assist the Wisconsin Department of Transportation (WisDOT) and other State agencies, examples from several States are organized into a template for preparing a bridge PM plan that includes the essential features of a systematic process. The results are expected to help State agencies understand and apply the concepts when establishing bridge PM programs and prepare proposals to obtain approval to use HBP funds for bridge preventive maintenance projects.
36 p.
Keywords: Asset management; Bridge maintenance; Preventive maintenance; Highway bridges; Safe, Accountable, Flexible, Efficient Transportation Equity Act: A Legacy for Users; SAFETEA-LU; Service life